Harmony, Power, and Diversity: The Concept of Multicultural Leadership in Serat Nitisruti - Ahmad Sodikin; Izzuddin Rijal Fahmi; Laila Tri Nurmasari; Miftahul Khoiri (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2026)
The increasing complexity of Indonesia’s plural society demands a model of leadership that is not only structurally effective but also inclusive in managing cultural, religious, and social identity diversity. However, studies on multicultural leadership are still dominated by Western theories, while explorations of local wisdom remain relatively limited. In fact, Nusantara traditions such as Serat Nitisruti by Pangeran Karanggayam contain teachings on the gusti-kawula relationship, social harmony, and the legitimacy of power based on morality. The scope of this research is focused on interpreting the relationship between social harmony, the legitimacy of power, and the management of cultural diversity as represented in the text. The purpose of this study is to uncover the model of multicultural leadership offered by Serat Nitisruti and its relevance within the context of a plural society. This study employs a qualitative research design with a textual analysis approach, hermeneutics, and cultural studies to interpret the symbols, normative teachings, and leadership values contained in the manuscript. The results indicate that Serat Nitisruti represents a leadership model that emphasizes a balance between power and ethics, as well as the leader’s ability to maintain harmony amid social and cultural diversity. Leadership is understood as non-dominative, but rather participatory and oriented toward justice, wisdom, and self-restraint. Therefore, Serat Nitisruti offers a multicultural leadership paradigm grounded in Javanese local wisdom that places harmony and diversity as the foundation of the legitimacy of power, thereby holding conceptual relevance for the development of inclusive leadership in contemporary Indonesia.